Seismic Performance and Risk Assessment of Industrial Structures during the 2023 Türkiye Earthquakes - Öztürk, Sezer; Altınsu, Elif; Güneş, Oğuz; Sarı, Ali (WCEE2024, 2024)
In the 2023 Kahramanmaras earthquake sequence, various types of damage occurred in a large number of different types of structures. Industrial structures are also among the structural types affected by this disaster. After this devastating earthquake, the research team conducted field surveys in provinces such as Hatay and Gaziantep and examined the seismic performance of industrial buildings in addition to ordinary buildings. In this paper, the investigations and the outcomes obtained for storage tanks and grain-like material silos are discussed. In a cylindrical storage tank that is located in a vegetable oil storage facility, liquid sloshing eventuated due to severe shaking, and the tank wall and roof were damaged. It has also been observed in tanks that elephant foot buckling occurred on the wall due to ground motion. The storage tank, which was overturned due to anchorage failure, is another damaged structure encountered during the examinations. The behaviour of these tanks also gives an idea about the behaviour of the tank in which flammable liquids are stored. Studies were also carried out on risk assessment, mitigation, and management for storage tanks with the data obtained. In addition, numerous distinct types of damage were encountered in the silos at the maize storage facility. Some silos were completely overturned, anchorage and wall damage occurred in several silos, and it was deduced that the plant suffered significant economic damage due to the spillage of the stored maize. It has been comprehended that the silo anchors are not designed to withstand possible seismic effects. The causes of the damages are explained by associating them with the seismic data recorded in the region, and the precautions that can be taken against earthquakes that may occur in the future are presented.